2018
DOI: 10.1021/jacs.7b09316
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective Inhibitors of 8-Oxoguanine DNA Glycosylase

Abstract: The activity of DNA repair enzyme 8-oxoguanine DNA glycosylase (OGG1), which excises oxidized base 8-oxoguanine (8-OG) from DNA, is closely linked to mutagenesis, genotoxicity, cancer, and inflammation. To test the roles of OGG1-mediated repair in these pathways, we have undertaken the development of noncovalent small-molecule inhibitors of the enzyme. Screening of a PubChem-annotated library using a recently developed fluorogenic 8-OG excision assay resulted in multiple validated hit structures, including sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 53 publications
5
86
0
Order By: Relevance
“…Yet this situation is ideal in the case of a synthetic lethality interaction between the pathologic context and DNA glycosylase [58,59]. Over the last few years, the search for inhibitors of DNA glycosylases hNeil1 (hNeil2) and hOgg1 has become a very active field [18][19][20][21]56,60,61]. We started this research in 2014 by discovering that 2-thioxanthine is an irreversible inhibitor of the bacterial enzymes Fpg and Nei and the human enzyme hNeil2, three enzymes belonging to the Fpg/Nei DNA glycosylase structural superfamily having a zinc finger (ZnF) [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet this situation is ideal in the case of a synthetic lethality interaction between the pathologic context and DNA glycosylase [58,59]. Over the last few years, the search for inhibitors of DNA glycosylases hNeil1 (hNeil2) and hOgg1 has become a very active field [18][19][20][21]56,60,61]. We started this research in 2014 by discovering that 2-thioxanthine is an irreversible inhibitor of the bacterial enzymes Fpg and Nei and the human enzyme hNeil2, three enzymes belonging to the Fpg/Nei DNA glycosylase structural superfamily having a zinc finger (ZnF) [18].…”
Section: Discussionmentioning
confidence: 99%
“…While recent studies have demonstrated the relevance of the research to design innovative anticancer strategies, only a few reported the search for hOgg1 and hNeil1 inhibitors [18][19][20][21]. In previous work, we initiated this study on DNA glycosylases from the structural Fpg/Nei superfamily [18,22,23].…”
Section: Reactive Oxygen Species (Oh• Omentioning
confidence: 99%
“…Dosimetry was done using a Unidos dosemeter equipped with a soft X-ray ionisation chamber TM23342A (PTW, Freiburg, Germany) applying a correction factor (1.2) for the dose increase at the glass surface. For inhibition of BER pathway methoxyamine hydrochloride (20-35 mM) 59 , OGG1 inhibitor_O8 (50-75 µM) 60 and CRT0044876 (150-240 µM) 61 (all purchased from Sigma-Aldrich) were incubated with cells 1-2 h prior to irradiation as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Only recently these obstacles have been overcome for OGG1 by the development of a potent first in class compound series by Tahara et al [50]. However, it remains to be seen how these unusual nonpolar molecules behave in different cell lines and ADME studies.…”
Section: Known Ber Inhibitorsmentioning
confidence: 99%